2020
DOI: 10.1002/pat.4986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multivalent cations on membrane‐foulant and foulant‐foulant interactions controlling fouling of nanofiltration membranes

Abstract: Insight was gained into the various factors influencing membrane fouling in the presence of different cations. Membrane‐foulant interaction energies were computed from contact angle measurements following the Lifshitz‐van der Waals/acid‐base approach. A unique approach was used to investigate cake‐enhanced concentration polarization (CECP) effects. Calcium worsened organic fouling through organic‐calcium complexation and increasing foulant affinity for the membrane surface, whereas magnesium and lanthanum had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…As shown in Figure 2c, the absolute value of zeta potential gradually decreased with the increase in calcium ion concentration, implying that the SiO 2 NP-NOM mixture will become more unsteady and more accessible for aggregation at higher concentrations. This phenomenon is in agreement with previous studies, which reported that calcium ions could reduce the negative charge of SiO 2 NPs or NOM [27,30,46]. This is attributed partly to double-layer compression and charge screening, and partly to the complexation of calcium ions with the carboxylic groups on the surface of the SiO 2 NP-NOM mixture resulting in charge neutralization.…”
Section: Effects Of Solution Chemistry On Physicochemical Properties ...supporting
confidence: 93%
See 2 more Smart Citations
“…As shown in Figure 2c, the absolute value of zeta potential gradually decreased with the increase in calcium ion concentration, implying that the SiO 2 NP-NOM mixture will become more unsteady and more accessible for aggregation at higher concentrations. This phenomenon is in agreement with previous studies, which reported that calcium ions could reduce the negative charge of SiO 2 NPs or NOM [27,30,46]. This is attributed partly to double-layer compression and charge screening, and partly to the complexation of calcium ions with the carboxylic groups on the surface of the SiO 2 NP-NOM mixture resulting in charge neutralization.…”
Section: Effects Of Solution Chemistry On Physicochemical Properties ...supporting
confidence: 93%
“…The contact angles of the PES UF membrane and the SiO 2 NP-NOM mixture were measured using a contact angle analyzer (JC2000C Contact Angle Meter, Shanghai Zhongchen Experiment Equipment Co. Ltd., Shanghai, China) based on the sessile drop method [23,28,29]. The SiO 2 NP-NOM mixture was first deposited on the PES UF membrane using the deadend stirred-cell filtration system, and then subjected to contact angle measurement [30]. The measurement of contact angle was performed at the time of two seconds after the liquid drop formed on the clean PES UF membranes or the PES UF membranes covered with SiO 2 NP-NOM mixture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower impact of Mg 2+ ions on HA fouling could also be linked to the high affinity of Mg 2+ ions for water molecules and its strongly held hydration shell, which weakens its interaction with HA compared with Ca 2+ [ 53 ]. In contrast to many studies reporting a higher fouling impact of HA foulants in the presence of Ca 2+ , studies have also reported a superior charge screening effect and charge density of Mg 2+ to cause more severe fouling compared to Ca 2+ [ 3 , 54 ]. However, cation interactions with NOM and associated fouling are highly dependent on NOM content, feed water chemistry, membrane surface properties, and operating parameters of nanofiltration [ 5 ].…”
Section: Resultsmentioning
confidence: 95%
“…Importantly, silicon concentrations in municipal secondary effluents ,,, can be higher than typical surface and groundwaters and seawater, , which in conjunction with proteins and alginates/polysaccharides can amplify fouling of membranes employed for potable reuse. ,, Another consideration is that anthropogenic organosilicon compounds have been identified in wastewater effluents, , whose role in fouling is only beginning to be delineated . Therefore, information derived from seawater and brackish groundwater desalination is not directly applicable to potable reuse because of the extremely high degree of resilience required for DPR, and additional investigations of RO/NF fouling under representative conditions are imperative. ,, …”
Section: Introductionmentioning
confidence: 99%